2005
DOI: 10.1038/sj.cdd.4401579
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium red-mediated suppression of Bcl-2 loss and Ca2+ release initiated by photodamage to the endoplasmic reticulum: scavenging of reactive oxygen species

Abstract: The photosensitizer 9-capronyloxytetrakis (methoxyethyl) porphycene localizes predominantly in the endoplasmic reticulum (ER) and, to a lesser extent, in mitochondria of murine leukemia L1210 cells. Subsequent irradiation results in the loss of ER 4 mitochondrial Bcl-2 and an apoptotic response. Although an increase in cytosolic Ca 2 þ was observed after irradiation, apoptosis was not inhibited by either the presence of the calcium chelator BAPTA or by the mitochondrial uniporter inhibitor ruthenium amino binu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 45 publications
4
36
0
Order By: Relevance
“…The ER is a known repository of calcium ions [16], and it seemed possible that ER photodamage might release sufficient Ca 2+ to result in interactions with the mitochondrial matrix that would lead to apoptosis. A study of the effect of ER photodamage on calcium fluxes [17] revealed several unexpected results.…”
Section: Apoptotic Responses To Pdt: the Role Of Bcl-2mentioning
confidence: 99%
“…The ER is a known repository of calcium ions [16], and it seemed possible that ER photodamage might release sufficient Ca 2+ to result in interactions with the mitochondrial matrix that would lead to apoptosis. A study of the effect of ER photodamage on calcium fluxes [17] revealed several unexpected results.…”
Section: Apoptotic Responses To Pdt: the Role Of Bcl-2mentioning
confidence: 99%
“…We have now examined the ability of salubrinal to protect murine leukemia L1210 cells from another inducer of ER stress: photodamage mediated by a porphycene termed 'CPO' that binds to the ER [3]. Irradiation of cells containing CPO initiates apoptosis as a result of photodamage to the anti-apoptotic protein Bcl-2 associated with the ER [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used two photosensitizing agents: the chlorin termed NPe6 is known to target lysosomes but not Bcl-2, and mediates apoptosis via activation of the pro-apoptotic protein Bid [11]. The porphycene CPO does target Bcl-2 associated with the ER [3]. Irradiation of cells containing NPe6 did not alter Bcl-2 levels (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3) and elsewhere (1) suggested that the porphycene CPO is initially bound to the ER. Because these data are only qualitative, it is difficult to assign definitive localization patterns solely on the basis of such studies.…”
Section: Discussionmentioning
confidence: 99%